Enhanced sliding mode controller design via meta‐heuristic algorithm for robust and stable load frequency control in multi‐area power systems - Tran, Anh‐Tuan; Duong, Minh Phuc; Pham, Nhat Truong; Shim, Jae Woong (IET generation, transmission & distribution, 2024)
This article introduces a novel approach named HBA‐dHoSMO, which combines a continuous decentralized higher‐order sliding mode controller‐based observer (dHoSMO) with the honey badger algorithm (HBA), specifically designed for load frequency control in multi‐area power systems (MAPSs). Traditional sliding mode controllers (SMCs) employed in load frequency control of MAPSs often face challenges related to chattering and oscillations, leading to decreased robustness and stability. Additionally, tuning the parameters for these SMC designs to achieve optimal performance in MAPSs can be challenging. The HBA‐dHoSMO is proposed to address the issues of chattering and oscillations, while the optimal parameters for SMC design are obtained using HBA. The stability analysis of the entire system is conducted using linear matrix inequality and the Lyapunov stability theory, affirming the reliability and feasibility of the approach. A comprehensive set of case studies is performed under various configurations and conditions. Additionally, particle swarm optimization and tuna swarm optimization, in conjunction with SMC‐based and proportional–integral–derivative controllers, are examined for performance comparison. Simulation results demonstrate the superior performance of the proposed controller across all case studies. This is evidenced by the lowest integral time absolute error values recorded as 0.0133, 6.45 ×  10−4, and 0.0167 for single‐, two‐, and three‐area power systems, respectively. This paper proposes a novel approach named HBA‐dHoSMO for load frequency control in multi‐area power systems. It combines a decentralized higher‐order sliding mode controller‐based observer (dHoSMO) with the honey badger algorithm (HBA). HBA‐dHoSMO addresses challenges associated with sliding mode controllers, optimizes parameters using HBA, and demonstrates superior performance with low integral time absolute error values across various power system configurations.